Pengaruh Pengungkapan Corporate Social Responsbility dan Mekanisme Corporate Governance terhadap Kinerja Keuangan:Studi pada Perusahaan Consumer Non-Cyclicals yang Terdaftar di BEI Tahun 2018-2022 - Yovie Santria; Erly Mulyani (Jurnal Eksplorasi Akuntansi, 2023)
This study will examine the relationship between corporate social responsibility disclosure and corporate governance mechanisms on financial performance. The scope of the study encompasses companies in the consumer non-cyclical sector, with a selected sample of 32 firms using purposive sampling methodology. The study involves analyzing 113 companies listed on the Indonesia Stock Exchange during the period from 2018 to 2022. Secondary data is employed for analysis, and the SEM-PLS method is applied. The results showed that CSR disclosure has a negative and insignificant effect on financial performance. The corporate governance mechanism has a positive and significant effect on financial performance.